THE EFFECT OF CORONA PANDEMIC, MINE COMMODITY PRICES AND RUPIAH EXCHANGE RATE ON INDONESIAN SHARIA SHARE PRICES IN THE MINING SECTOR 2020 - Awwal, Muhammad Al Faridho; Afandi, Mukhamad Yazid (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
This study aims to analyze the effect of the corona pandemic, mining commodity prices and the rupiah exchange rate on Indonesian Islamic Share Prices/Indeks Saham Syariah Indonesia (ISSI) in the mining sector in 2020. The corona pandemic is represented by daily active cases that occur in Indonesia, the mining commodities used are coal, oil and gold prices world, and the exchange rate of the rupiah against the dollar. The data used is a cross-sectional type with a sample of 32 companies with an observation duration of 195 days during the 2020 period. The results show that simultaneously the independent variables significantly affect the dependent variable and partially the world coal price, world oil price, gold price. The world and the rupiah exchange rate with the exception of corona have a significant effect on mining stock prices at Indonesian Islamic share prices in 2020. This research proves that the Market anomaly theory is proven to occur in 2020 as a result of the corona pandemic, anomaly in commodity prices and exchange rates on the Indonesia Stock Exchange, especially in the Indonesian Islamic share prices mining sector which proves that the market cannot be accurately predicted if it occurs a sentiment strong enough globally to move investors both in terms of selling or buying shares that previously could not be reflected by the company's stock price.